Stratigraphic framework of the late Miocene to Pliocene Pisco Formation at Cerro Colorado (Ica Desert, Peru). Issue 3 (26th May 2016) - Di Celma, C.; Malinverno, E.; Gariboldi, K.; Gioncada, A.; Rustichelli, A.; Pierantoni, P. P.; Landini, W.; Bosio, G.; Tinelli, C.; Bianucci, G.
Abstract : This paper describes a ∼200 m-thick section of the Pisco Formation exposed at Cerro Colorado, an important fossiliferous site in the Ica desert. In order to properly place the fauna in its correct relative position, this study establishes the stratigraphic framework within which the different fossil-bearing intervals of this site can be compared and may prove invaluable in future high-resolution studies on the faunal change. Most of the Pisco Formation deposits exposed at Cerro Colorado consist of gently dipping fine-grained sandstones, diatomaceous siltstones and diatomites with minor ash layers and dolomites deposited within nearshore and offshore settings. To facilitate detailed stratigraphic correlations within the Pisco strata for a 30 km 2 area, eight marker beds have been defined and large-scale (1:10, 000 scale) geological mapping conducted to determine fault positions, styles and offsets. The geological map shows that there are two important angular unconformities in the study area. The first one is the interformational basal unconformity of the Pisco Formation against folded, faulted, and planated Oligo-Miocene rocks of the Chilcatay Formation. The second is a low-angle intraformational erosional discontinuity of up to 4° angular discordance that allows the subdivision of the Pisco stratigraphy exposed in the study area into two informal allomembers. Dating of the exposed succession by diatom biostratigraphy suggests that the age of the lower allomember is late Miocene, whereas the upper allomember is late Miocene or younger.